PERBANDINGAN PENGETAHUAN MASYARAKAT TENTANG ANTIBIOTIK DALAM PENGGUNAAN OBAT RASIONAL MELALUI MEDIA WHATSAPP DAN LEAFLET DI KECAMATAN SINGKIL TAHUN 2019 - NETTY AFRIANI POHAN; WISNU HIDAYAT; JASMEN MANURUNG (LP2MTBM MAKARIOZ, 2022)
The public needs to be educated about the use of antibiotics in rational drug use because it has a high level of risk. The study aimed to determine the differences before and after given knowledge about antibiotics in rational drug-use through WhatsApp and leaflet media. The design of the research is quasi-experimental with primary data obtained by distributing questionnaires and secondary data collected from the data of Singkil District and other literature. The number of samples was 44 respondents, each of which was 22 respondents for the WhatsApp groups and leaflet groups. Data analysis uses univariate data, which is useful for describing variables, and bivariate data explains the hypothesis of the relationship between independent and dependent variables. The results of the analysis showed a significant difference in the knowledge of antibiotics in rational drug-use before and after health education was given by the social media WhatsApp and leaflets with p-values ​​of 0,000 each. The analysis also shows that there is a significant difference in the knowledge of antibiotics in rational drug use before and after health education is given between via social media WhatsApp and leaflets with a p-value of 0.039, where train through social media WhatsApp is more effective than through leaflets. Suggestions to the Public healths are expected to be able to choose and determine which education media are more effective given to the community in the delivery of information about antibiotics in rational drug use, to the researchers further it is recommended to make comparisons related to other extension media, for example comparing pocketbook media with audiovisual media.